PENGARUH GEOMETRI DAN PENAMBAHAN JUMLAH SIRIP TERHADAP DISTRIBUSI TEMPERATUR HEAT SINK SEBAGAI ALTERNATIF PENDINGINAN PADA PIRANTI ELEKTRONIK - Subekti, Fajar; Wahyudi, Slamet; Gapsari, Femiana (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
This study aims to determine the effect of the geometry shape of the copper material heat sink fins on the surface temperature distribution of the heat sink. The material used in this research is pure copper, the shape of the heat sink fins is made rippled with the addition of the number of fins 5, 6, and 7 and the input temperature is varied from 40 C to 80 C with airflow variations from 0.2 m/s to 1 m/s. The first step is to create a heat sink design with Autodesk Inventor. Then the plan is simulated with Autodesk CFD to solve the continuity, momentum, turbulence, and energy equations. Based on the method that has been carried out, it is found that the addition of variations in the number of fins affects the decrease in surface temperature. The highest temperature drop on fin 5 ripples is 24.1 C. The heat energy transfer rate increased by 0.4657 W. The convection heat transfer coefficient increased by 3.47 W/m²C. Nusselt number shows an increase of 271. Fin performance has increased efficiency by 63.4 %, and effectiveness by 1.61. The results of this study are expected to provide practical alternatives that can be widely adopted on a heatsink plate that is very promising for future thermal developments.